Elimination of voids by laser remelting during laser cladding Ni based alloy on gray cast iron. (15th April 2019) - Li, Yongjian; Dong, Shiyun; Yan, Shixing; Liu, Xiaoting; Li, Enzhong; He, Peng; Xu, Binshi
Graphical abstract: Highlights: Voids in the interface zone were successfully eliminated by laser melting process. Microstructure and phase evolution were determined in the transition zone. Mechanism of the elimination process was studied. Abstract: Gray cast iron was a traditional iron material which had been applied to industrial field for many years. For damaged gray cast iron, the repair process is very difficult because the gray cast iron was easy contaminated due to its special loose structure and the contaminants were difficult to remove. The strong tendency of the void formed in the interface region was a major trouble for the laser cladding process. In this paper, in order to eliminate those voids, laser cladding process on gray cast iron with remelting process was successfully carried out. The generation mechanism and elimination process of the voids were determined. The microstructure evolution in the melted zone (MZ), partially melted zone (PMZ) and heat affected zone (HAZ) was also researched. Optical microscopy (OM) and Scanning electron microscopy (SEM) were used to identify the microstructure and phase composition of the cladding layers and the transition zones. The results revealed that laser remelting was an effective way to eliminate the voids generated in the interface zone. The average microhardness of the hardened region formed during multi-layer cladding with remelting was about 600HV, and the width of the hardened region ranged from dozens of microns to hundreds of microns.